Accent Anxiety Among Efl Students - Hanifah, Nifa; Anjely, Asnaul Husna Tenri Baji; Arofah, Dinda Anggita Nurul (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to explore the experiences and perceptions of EFL (English as a Foreign Language) students towards accent anxiety or anxiety due to non-native accent in English language learning. The research was conducted on five students of English Education Study Program in University of Kuningan using descriptive qualitative method through interviews. The data were analyzed using thematic analysis approach method. The results showed that most of the participants experienced anxiety, insecurity, and fear of negative judgment because their accents were considered not up to native speaker standards. This anxiety was also triggered by the difficulty of understanding other accents, the desire to imitate certain accents (such as American and British), as well as the perception that accents could affect others' judgment of their English proficiency. Although most of the participants prioritized clarity of communication, they still hoped to sound like native speakers. Support from the surrounding environment, especially lecturers and friends, proved to play an important role in reducing anxiety. This study confirms the importance of the World Englishes approach in English language teaching, which emphasizes clarity and acceptance of accent diversity.